2016
DOI: 10.1038/srep36851
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Structural Connectivity of the Default Mode Network in Dogs using Diffusion Tensor Imaging

Abstract: Diffusion tensor imaging (DTI) provides us an insight into the micro-architecture of white-matter tracts in the brain. This method has proved promising in understanding and investigating the neuronal tracts and structural connectivity between the brain regions in primates as well as rodents. The close evolutionary relationship between canines and humans may have spawned a unique bond in regard to social cognition rendering them useful as an animal model in translational research. In this study, we acquired dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
0
15
1
Order By: Relevance
“…Only one RSN, the DMN, does not match in both studies. While our results correspond to the results of Kyathanahally et al [16], that showed dissociated DMN in dogs in rs-fMRI as well as in DTI [53], this could not be reproduced by Szabó and colleagues [17]. [12,60].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Only one RSN, the DMN, does not match in both studies. While our results correspond to the results of Kyathanahally et al [16], that showed dissociated DMN in dogs in rs-fMRI as well as in DTI [53], this could not be reproduced by Szabó and colleagues [17]. [12,60].…”
Section: Discussioncontrasting
confidence: 80%
“…Weaker connectivity between the anterior and posterior component in dogs has been supported using diffusion tensor tractography, which only identified white matter tracts connecting medial prefrontal cortex/anterior cingulate cortex to the posterior cingulate cortex in 9/23 dogs [53], while in humans these tracts were identified in 22/23 subjects [54]. This was also reflected by a significantly lower group fractional anisotropy in dogs in this area compared to humans [53]. Dissociation of the DMN has been found in children and in patients with Alzheimer's diseases and may reflect a lower level cognitive processing [52].…”
Section: Discussionmentioning
confidence: 99%
“…While the DWI population template was upsampled to 0.5 mm 3 using advanced processing methods for structural connectome creation, these techniques use a significant amount of interpolation potentially biasing the data with artificial inflation. Higher-resolution DTI imaging has been achieved at higher field strengths or at the compromise of the number of diffusion directions (Zakszewski et al, 2014;Robinson et al, 2016;Hutchinson et al, 2017). In order to ensure that the lower resolution did not compromise the resulting tractography reconstructions, we validated our results by comparing our tract reconstructions to gross anatomic white matter dissections.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the cat being a widespread preclinical animal model in neuroscientific research, this species lacks the open-source stereotaxic MRI-based brain atlases available in other species (Mori et al, 2008;Jiang and Johnson, 2011;Rumple et al, 2013;Zakszewski et al, 2014;Robinson et al, 2016). The only open-source stereotaxic feline MRI atlas currently available is created with structural T1-weighted MRI data and focuses on cortical and deep gray-matter structures (Stolzberg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation